Um ambiente de e-commerce voltado a microempreendedores - Santos, Igor Fernandes dos (Universidade Federal Rural do Semi-Árido, 2020)
This work presents the development of a prototype of a Web Single- Page Application (SPA) system to assist in the business management of micro entrepreneurs in Mossor´o / RN. The system was developed using the knowledge acquired in the computer science course, in particular Software Engineering and Web Development.
Keywords: Marketing digital; E-commerce; Plataforma web; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO